INVESTOR REACTION ANALYSIS OF LEGISLATIVE ELECTION EVENTS APRIL 9 AND THE PRESIDENT OF THE REPUBLIC OF INDONESIA JULY 9 2014 - Oktaviana, Hilda; Adib, Noval (Jurnal Ilmiah Mahasiswa FEB, 2016)
The objective of the research is to test the information content of the Legislative election on 9th  April and the Presidential election of 9th  July 2014. The presence or absence of information content of the event reflects the presence of market or investor reaction. The market reaction can be measured with the amount of profit, namely return and abnormal return. The research samples are taken using the method of purposive sampling, and there are 45 stock companies included in the LQ-45 index in 2014. The statistical test used by the research is T-test (Paired two Samples for Mean).  The  observation  periods  are  divided  into  5  and  10  days  before  the  legislative  and presidential election, and 5 and 10 days after the event. The research results show that there is an increase in the profit level which is measured with stock return 10 days after the legislative election, while in the preiod of 5 days after the legislative election, stock return remains in the same point. However, when measurement is conducted using abnormal return, the result shows that no investor gains abnormar return both 5 days and 10 days after the election. Meanwhile, stock return during the period of 5 and 10 days after the presidential election experience a decrease and there is no investor gaining abnormal return on the same period.   Keywords:  Legislative General Election, Presidential Election, Stock Return and Abnormal Return